IMPLEMENTASI METODE BAGI HASIL DENGAN PRINSIP MUDHARABAH PADA BANK SYARIAH DI INDONESIA DIHUBUNGKAN DENGAN FATWA DSN NO. 15/DSN-MUI/IX/2000 - Hermansyah Hermansyah (Universitas Suryakancana, 2018)
Today Islamic economy was recognized and growing in daily life, particularly Indonesia, both in real sector and financial sector. One of financial organization which has significant role in satisfying social need is bank, particularly Islamic bank. The operational base of Islamic bank was settled in Law No. 21 of 2008 about Islamic Bank. Dual banking system framework applied in Indonesia offer more alternatif option that can be chosed by Indonesian people. One of Islamic bank operational system is revenue sharing which can be applied in two method: profit sharing and revenue sharing. The research use a normative juridical approach that designed to find positive legal principles, analytical descriptive. The data collection techniques use literature study and field study, determination of sample in purposive sampling way and the data analysis using qualitative normative analysis. From research result can be conclused that first in law of Islamic economy, the profit sharing and revenue sharing methods is allowed by Islam law principle, second, application of mudharabah to customer savings in Islamic bank have two meanings; first, mudharabah as a product is applied to accumulation of funds, generally Islamic bank use revenue sharing and second, mudharabah as a system by which mudharabah is general guidelines for Islamic bank in performing various transaction of available banking product.Keywords: The Implementation Of Profit Sharing Method, Mudharabah Principle, Islamic Bank, Fatwa DSN No. 15/DSN-MUI/IX/2000.